Abnormal pattern detection in PPG signals during sports and exercises. Issue 3 (13th October 2020) - Quan, Long; Wu, Yunming
Abstract : Pulse oximeter is an important clinical equipment, which can measure the photoplethysmogram (PPG) signal to calculate the heart rate, blood volume, breathing, hypovolemia etc. However, the PPG signal is easily interfered by some factors, such as body movement in sports or exercises. Before calculating the heart rate, blood volume, breathing, or hypovolemia, we need to recognize these interfered segments. In order to identify these abnormal patterns, the PPG signal is converted as a symbol sequence which consists of several characters. Then, the segment of PPG signal is represented as a character sequence. The abnormal pattern in PPG signal is detected by the distance between character sequences which are obtained from local and global information. When the distance is great than a threshold, the segment is regarded as an abnormal pattern. The proposed method also can be used in other physiological signals.